The invention of identity of Mato Grosso do Sul State in a theater of a technical school - doi: 10.4025/actascieduc.v35i2.19067 - Rosemeire de Lourdes Monteiro Ziliani (Universidade Estadual de Maringá, 2013)
Current study socializes analyses on the programs of a twenty-year-old theater group in a technical school in Aquidauana MS Brazil, by discussing the discourse of written and rehearsed plays, underscoring the stance of young people who participated as actors. Studies featuring Foucauldian perspectives were employed to problematize and discuss the selected material. Architectural, psychopedagogical, agricultural and artistic discourses crisscrossed in the Institution´s programs to prepare agents to be technicians within the primary sector of the local economy. However, the school theater had a more comprehensive task, or rather, to define or invent an identity of the state of Mato Grosso do Sul after its separation from the state of Mato Grosso in the late 1970s. The statements of the young actors on the discourses and practices that marked the theater experience showed different forms of appreciation and different ways to subjective them.